Jumping to the Head of the Invisible Line: Queuing and Waiting in Electronic Ticket Systems. (October 2019) - Seeley, J. Lotus
Research on queuing and waiting has demonstrated how these practices exemplify tacit norms of social organization and how the dynamics of deference embedded in waiting (re)produce the status of the waiting individual and/or the power of individuals in charge of queues. Less attention has been given to the broader effects of the agentic efforts of individuals to decrease their wait times and increase their priority in their original queue, what I term the active management of waiting . Using ethnographic and interview data on IT support workers at a large university, I document how high-status individuals engage in three active management of waiting strategies: trumping the queue, circumventing the queue, and refusing to queue. As I show, these strategies are patterned by organizational status and thus not only (re)produce the status of the waiting individual but also exert a disciplinary effect on servers and help (re)produce organizational status structures as a whole.